Street Stops and Police Legitimacy: Accountability and Legal Socialization in Everyday Policing of Young Adults in New York City, 2011-2013 - Tyler, Tom ([Verlag nicht ermittelbar], 2017)
These data are part of NACJD's Fast Track Release and are distributed as they there received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except of the removal of direct identifiers. Users should refer to the accompany readme file for a brief description of the files available with this collections and consult the investigator(s) if further information is needed. This study interviewed young men living in New York City about their experiences being stopped by the police on the street or in their cars. It examined how experience with the police as well as general evaluations of police policies, practices and behaviors in the respondent's neighborhood shaped views about police legitimacy, and law related behavior, such as compliance with the law and cooperation with legal authorities.